Influence of Intrinsic and Extrinsic Plasminogen upon the Lysis of Thrombi In Vitro - Nishino, N; Kakkar, V V; Scully, M F (Thrombosis and Haemostasis, 1991)
When the rate of lysis of artificial thrombi (prepared from plasma or whole blood) was expressed according to the concentration of tissue type plasminogen activator (t-PA) or single chain urokinase type plasminogen activator (sc-uPA) then bell-shaped dose response curves were obtained, low rates being observed at concentrations of activator greater than 500 units/ml. Bell-shaped dose response curves were not observed for rate of lysis of artificial thrombi over the concentrations of streptokinase tested (SK) or for the lysis of plasma gel clots by any of the activators tested. Further investigation indicated that the preponderant mechanism for dissolution of thrombi at 500 units/ml of t-PA was by activation of the plasminogen within the thrombus (intrinsic) since the plasminogen present in the plasma perfusing the thrombus (extrinsic) rapidly became depleted. On the other hand, at 50 units/ml t-PA the lysis was observed to be due preponderantly to the action of plasmin arising from extrinsic rather than intrinsic plasminogen. If "plasminogen enriched" thrombi were prepared in the presence of Lys plasminogen (Lys-Plg) faster rates of lysis occurred and bell-shaped biometric curves were not observed.